Academic Management Towards Promoting Student Competency - Tanadechpumsit, Chayanis; Oui-panich, Thawatchai; Prasongsang, Chaiwat (Ph.D. in Social Sciences Journal, 2026)
This article presents an approach to academic administration aimed at fostering students' competencies in alignment with global transformations, emphasizing the significance of 21st-century education, which focuses on developing 'global citizens' equipped with essential life and work skills. Anchored in the Basic Education Core Curriculum B.E. 2551, which delineates five key competencies—communication, thinking, problem-solving, life skills, and technology utilization—this study examines how school-based academic administration promotes these competencies. The scope of this examination includes curriculum and instructional management, assessment and research, the development of media and learning resources, supervision and guidance, quality assurance, community engagement, and personnel development. The analysis reveals that effective academic administration is a crucial factor in cultivating high-quality 'global citizens'. Covering five principal dimensions of academic administration, the analysis demonstrates the direct correlation and interconnection of these dimensions with the development of students' essential competencies, encompassing critical thinking, problem-solving, life skills, technological proficiency, and communication. The analysis highlights strategies to enhance academic administration that are oriented towards student competency development, such as active learning methodologies, authentic assessments, technology integration, and comprehensive stakeholder participation, to prepare students for the complexities of a rapidly evolving global landscape.